2013
DOI: 10.1007/s10059-013-2190-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic Acid Isolated from Lactobacillus plantarum Suppresses LPS-Mediated Atherosclerotic Plaque Inflammation

Abstract: Chronic inflammation plays an important role in atherogenesis. Experimental studies have demonstrated the accumulation of monocytes/macrophages in atherosclerotic plaques caused by inflammation. Here, we report the inhibitory effects of lipoteichoic acid (LTA) from Lactobacillus plantarum (pLTA) on atherosclerotic inflammation. pLTA inhibited the production of proinflammatory cytokines and nitric oxide in lipopolysaccharide (LPS)-stimulated cells and alleviated THP-1 cell adhesion to HUVEC by down-regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…The process of inflammation mediated by IL-1 can cause many kinds of diseases. [5][6][7] Long-term chronic inflammation can lead to the formation of arterial plaques as well as atherogenesis, 8 and active inflammatory process may trigger the rupture of plaque which increasing the risk of coronary thrombosis, then leading to clinical ischemic events. 9 There are four IL-1 blockers available now, anakinra, canakinumab, rilonacept, and gevokizumab.…”
Section: Introductionmentioning
confidence: 99%
“…The process of inflammation mediated by IL-1 can cause many kinds of diseases. [5][6][7] Long-term chronic inflammation can lead to the formation of arterial plaques as well as atherogenesis, 8 and active inflammatory process may trigger the rupture of plaque which increasing the risk of coronary thrombosis, then leading to clinical ischemic events. 9 There are four IL-1 blockers available now, anakinra, canakinumab, rilonacept, and gevokizumab.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of the lipids and oxLDL causes activation of innate and adaptive immunity leading to increased production of inflammatory cytokines and homing of inflammatory cells. Infection of the arterial intima with viruses and bacteria results in the production of pathogen-associated molecular patterns (PAMPs), such as lipopolysaccharides (LPS), peptidoglycans, and lipoteichoic acid (Chen et al 2013;Kim et al 2013;Thankam et al 2016) (Figures 2 and 3). Here, we have discussed the role of DAMPs and PAMPs and their interaction with inflammatory mediators in the pathogenesis of inflammation-mediated plaque vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that LTA of L. plantarum can modulate pro-inflammatory or anti-inflammatory responses. Subsequent studies showed other immunomodulatory features of L. plantarum LTA, such as the down-regulation of Shigella flexneri peptidoglycan-induced inflammation [43], or the suppression of LPS-mediated inflammation [44], among other effects. LTA function has also been studied in L. rhamnosus GG (LGG), one of the most studied probiotics [45].…”
Section: Other Cell-wall Componentsmentioning
confidence: 99%